Antecedents of Online Shopping: A Literature Review - Shakti Shukla, Uma, Anjali Dixit, (European Economic Letters (EEL), 2024)
The objective of undertaking this review is to identify the core factors which have an impact on the Online shopping behaviour of the customers. Current review is built on identifying the gaps and studying the findings of the research papers based on Online shopping. A body of 60 research papers was reviewed which investigated a plethora of antecedents of online shopping. Based on the review, we identify and propose six themes, pertaining to the concepts, methodologies and findings. The current study throws light on various determinants of consumer behaviour towards online shopping. A list of variables in the form of themes is studied and suggestions are made. It has also considered the customers’ behaviour towards the upcoming technologies like Virtual reality and Augmented Reality. The study will not only enhance the literature about the subject but will also provide cues to the marketers to build new strategies which can enhance the online shopping experience of the customers.